Partial replacement of cement with sewage sludge ash (SSA) in mortar - Wong, Yih Kang (2015)
One of the methods of sewage sludge disposal is incineration. Although the incineration process is able to reduce the volume of the sewage sludge, it is not a proper solution since the ash generated after the incineration process must be disposed to landfill. The aim of this research is to study the partial replacement of cement with sewage sludge ash, SSA in mortar through experimental works. The experimental works were carried out to access the feasibility of utilizing SSA as a construction material. An attempt has been made to replace 10% and 15% of the mass of cement with 600°C and 800°C incinerated SSA into the mortar. In this research, the sewage sludge is acquired from Indah Water Konsortium (IWK), sewage treatment plant in Kuantan, Pahang. The compressive strength and total porosity test were conducted by using 50 mm x 50 mm x 50 mm mortar cubes at the ages of 1, 7, 28 and 90 days. X-ray Diffraction (XRD), Xray Florescence (XRF) and Field Emission Scanning Electronic Microscope (FESEM) were carried out to determine the chemical composition and the microstructure of the sewage sludge, SSA and SSA mortar. The result of the compressive strength test shows that the mortar with 10% replacement of 800°C burnt SSA increase in compressive strength up to 1.14% and 5.06% at the ages of 28 days and 90 days, respectively. The total porosity of the mortar also decreases up to 7.05% after the replacement of 10% 800°C burnt SSA after 90 days. The XRD and XRF tests show that the major components in sewage sludge are SiO2, Al2O3 and Fe2O3. The incineration process triggered the formation of those oxides in SSA where SiO2, Al2O3 and Fe2O3 can act as pozzolan in cementatious materials. The particles of SSA are discrete spherical particle and have wide range of sizes i.e. from 3.5 μm to 35 μm. The formation of needle shape particles can be observed from the FESEM micrograph of SSA mortar which indicates the pozzolanic activities of SSA.